Republic of Poland : Background Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This Background Paper examines sources of net international reserve inflows for Poland. It shows that once estimate of unrecorded border trade is included, both the current and capital accounts are in surplus. The paper illustrates the methods through which estimates of unrecorded trade can be obtained. It offers a complementary view of Poland's inflation problem from a medium-term perspective. Specifically, the paper shows that relative price adjustment, combined with indexation and inertia, has been part and parcel of Polish inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet